Oral nicotine marketing claims in direct-mail advertising. Issue 5 (6th May 2021) - Czaplicki, Lauren; Patel, Minal; Rahman, Basmah; Yoon, Stephanie; Schillo, Barbara; Rose, Shyanika W
Abstract : Background: Little is known regarding how oral nicotine products (eg, nicotine pouches, lozenges) are marketed to consumers, including whether potential implicit reduced harm claims are used. In the current study, we explored the marketing claims present in a sample of direct-mail oral nicotine advertisements sent to US consumers (March 2018–August 2020). Methods: Direct-mail ads (n=50) were acquired from Mintel and dual-coded for the following claims: alternative to other tobacco products, ability to use anywhere, spit-free, smoke-free and product does not contain tobacco leaf. We merged the coded data with Mintel's volume estimate (number of mail pieces sent to consumers) and calculated the proportion of oral nicotine advertisements containing claims by category. Results: Of the 38 million pieces of oral nicotine direct-mail sent to US consumers, most featured claims that the product could be used anywhere (84%, 31.8 million pieces); was an alternative to other tobacco products (69%, 26.1 million pieces); and did not contain tobacco leaf (eg, 'tobacco leaf-free', 'simple' approach of extracting nicotine from tobacco; 55%, 20.7 million pieces). A slightly smaller proportion contained claims that oral nicotine was 'spit-free' (52%, 19.8 million pieces) or 'smoke-free' (31%, 11.7 million pieces). Conclusion: Our results provide an early indication of marketing claims used to promote oral nicotine. The strategies documented, particularly the use of language to highlight oral nicotine is tobacco-free, may covey these products as lower-risk to consumers despite the lack of evidence or proper federal authorisation that oral nicotine products are a modified-risk tobacco product . Future research is needed to examine consumer perceptions of such claims.